Entrepreneurship : theory, process, practice - Donald F. Kuratko (Boston, Massachusetts : Cengage, 2020)
Learn the true process of a successful entrepreneur with ENTREPRENEURSHIP: THEORY, PROCESS, PRACTICE, 11e! Presenting the most current thinking in this explosive field, this renowned entrepreneurship text provides a practical, step-by-step approach that makes learning easy. It incorporates up-to-the-minute information about trending topics such as The Lean Startup methodology and design innovation. The accompanying MindTap Learning Suite challenges you to apply what you've learned as you complete a unique set of activities designed to help you sharpen your entrepreneurial skills. You'll tackle activities that challenge you to experience the world of new venture creation or corporate innovation first hand. This book will be your guide to understanding the entrepreneurial challenges of tomorrow, and MindTap will teach you the necessary skills to become a leader in the industry.
Keywords: Entrepreneurship; Small business; New business enterprises